2023
DOI: 10.1609/aaai.v37i10.26429
|View full text |Cite
|
Sign up to set email alerts
|

Predicate Invention for Bilevel Planning

Abstract: Efficient planning in continuous state and action spaces is fundamentally hard, even when the transition model is deterministic and known. One way to alleviate this challenge is to perform bilevel planning with abstractions, where a high-level search for abstract plans is used to guide planning in the original transition space. Previous work has shown that when state abstractions in the form of symbolic predicates are hand-designed, operators and samplers for bilevel planning can be learned from demonstrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…We also tried the Slitherlink domain, which was featured in the 2023 International Planning Competition, and found that GPT-4 did not recognize that no simple strategy exists (Takayuki 2000). Generalized planning without LLMs also remains important in cases where domain descriptions are not human-readable, e.g., because the predicates or operators are learned (Silver et al 2023). Even with natural language descriptions, combining "classical" approaches with LLMs may be best.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…We also tried the Slitherlink domain, which was featured in the 2023 International Planning Competition, and found that GPT-4 did not recognize that no simple strategy exists (Takayuki 2000). Generalized planning without LLMs also remains important in cases where domain descriptions are not human-readable, e.g., because the predicates or operators are learned (Silver et al 2023). Even with natural language descriptions, combining "classical" approaches with LLMs may be best.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…In another line work, [20], [21], [22] proposed a bilevel planning schema in which a set of operators and corresponding samplers are learned from previously acquired symbols that allow the agent to make refined plans that can consider the geometric information. [23] learns predicates from demonstrations with a surrogate objective for planning. [24] learns policies parameterized by neural networks based on the symbolic state transitions.…”
Section: Related Workmentioning
confidence: 99%